Using Interactive Whiteboards (IWB) in the English Classroom as Supporting Technology in the Teaching and Learning Process: Opportunities and Challenges - Fitria, Tira Nur (Universitas Kapuas, 2024)
This research describes the teachers' and students' perception of using Interactive Whiteboards (IWB) and explain the opportunities and challenges of using IWB in English classrooms. This research uses library research. IWBs are large interactive displays used as input devices for computers. They can be used in educational institutions combining traditional presentation benefits with cutting-edge technology. IWB technology consists of a digital board, computer, and projector, which can be linked to a personal computer for easy use. It offers various tools including graphics, word processing, database, and multimedia tools. Using IWB as an educational tool increase new knowledge, provide innovations to students, improve the quality of students’ learning, facilitate interaction between teaching teams and students, improve teaching efficiency, and reduce paper usage. IWB has been found to significantly improve students' English skills, vocabulary proficiency, engagement, and attitude. However, implementing IWBs in schools presents challenges including large costs, insufficient technical support, technical issues, lack of adequate e-materials, limited time for lesson preparation, negative attitudes, lack of consensus among decision-makers, inadequate proficiency, and inadequate teacher training. Teachers need to master this technology so they can use it effectively in teaching. It is proposed that teachers receive training on utilizing IWBs more efficiently in various classroom settings. Teaching using proper operation of IWBs is a major factor in the teachers' ability to implement it successfully in the classroom. The trained teachers possessed a comprehension of the most efficient methods for utilizing the IWBs.